PEMANFAATAN POJOK LITERASI SEBAGAI MEDIA KREATIVITAS DALAM PENGEMBANGAN BAKAT SISWA MI MAMBAUL ULUM DAGAN - Putri Apriliya, Erika; Suradji, Muchamad; Nuzilatus Shoimah, Retno (-, 2025)
Good education can be seen from various things that include it. One of them can be seen from reading ability and interest. in order to provide quality education so that it can improve students' literacy skills. Literacy is not just about reading, counting and writing, but literacy can start with reading. Much of the educational process today depends on a person's literacy awareness and abilities. Good literacy can encourage a student to tend to solve problems well. MI Mambaul Ulum Dagan, as an educational institution that cares about the holistic growth of students, faces demands to enrich learning approaches with creative elements and talent empowerment. MI Mambaul Ulum has made literacy a gateway to exploring creative potential and developing talents in every child. Having a reading corner at MI Mambaul Ulum Dagan can make it easier for students to access books when they want to read, which can indirectly increase students' interest in reading. So this research focuses on exploring and utilizing literacy corners as a medium for creativity in developing student talents at MI Mambaul Ulum Dagan. From the above background, the researcher took the title "Utilization of Literacy Corners as a Media for Creativity in Developing the Talents of MI Mambaul Ulum Dagan Students". This research aims to determine the use of literacy corners as a medium for developing student creativity at MI Mambaul Ulum and to find out the results of using literacy corners to develop students' creativity and talents at MI Mambaul Ulum. In this research the author applies a qualitative descriptive approach with the aim of describing and understanding reality. the event that is the focus of the research. The data collection techniques used in this research are observation, interviews and documentation studies. The research results related to the use of literacy corners as a medium for developing creativity for MI Mambaul Ulum students show that the literacy corners at MI Mambaul Ulum have been successful in developing students' creativity and talents, marked by increased creative expression, talent development, learning motivation and critical thinking skills. It is hoped that with improved facilities and activities, the benefits of the literacy corner will continue to increase. The literacy corner at MI Mambaul Ulum has proven successful in increasing student creativity, as seen from the increased expression of creative ideas and active involvement in learning. With supportive reading materials, a strategic location, and activities that stimulate the imagination, the literacy corner creates a conducive environment for the development of creativity. This model is recommended for application in other schools. Meanwhile, the results of using the Literacy Corner to develop student creativity and talent at Mi Mambaul Ulum have proven successful in increasing student creativity, as seen from the increased expression of creative ideas and active involvement in learning. With supportive reading materials, a strategic location, and activities that stimulate the imagination, the literacy corner creates a conducive environment for the development of creativity. This model is recommended for application in other schools.